AB0730 Psoriatic Arthritis Patients with Work Disability Have Worse Quality of Life Compared To Those Who Are Employed. (15th July 2016) - Farkas, F.; Szentpetery, A.; Gallagher, P.; FitzGerald, O.
Abstract : Background: Work disability (WD) is an important functional outcome measure in inflammatory arthritis, which has been studied comprehensively in rheumatoid arthritis and ankylosing spondylitis, however limited data is available in psoriatic arthritis (PsA). A variety of WD measurement tools are available, but there are no validated and specific guidelines in PsA [1, 2]. Objectives: In PsA patients with and without WD: (1) to compare patient-reported outcomes (PROs) and physician-assessed measures and (2) to assess whether there are gender-specific differences associated with WD. Methods: Consecutive patients with PsA fulfilling the CASPAR criteria were enrolled. Patients on disability pension, those with early retirement due to arthritis, those unemployed, away from work due to sick leave were considered as having WD. Disease activity measures (TJC/68, SJC/66, ESR, CRP, PASI), economic data, patient-reported outcome measures (HAQ, EQ-5D, SF-36, BASDAI, BASFI, ASQoL, DLQI, pain VAS, average level of fatigue), radiographic damage, medication history and comorbidities were compared between employed and work-disabled patients in both genders using Mann-Whitney pairwise and chi-square test. Results: 81 patients completed the economic questionnaire. Thirty-eight (17 male and 21 female) participations of working age had work disability versus forty-three (20 male, 23 female) employed patients. Out of 81 patients, 27 were biologic-naïve and 54 had ever been on biologic agents. We have found no significant differences in disease activity measures or in the number of erosions between work-disabled and employed patients. On the other hand patients with WD had significantly worse self-reported values in both gender groups, especially in females. The total number of comorbidities (p=0.020) and coexistent rheumatic diseases (p=0.025) were significantly higher among patients with WD. Work-disabled patients had more healthcare-related appointments and required more help (p=0.001), including home care and assistance travelling to the hospital. Conclusions: Consistent with previous studies, in this cross-sectional cohort we have observed that rates of WD are high (46.9%) among patients with PsA with no difference between males and females. Despite similar disease activity and structural damage measures, patients with WD had worse physical function and overall reduced quality of life compared to employed patients. These differences were more pronounced in females, who had more physical and social limitations related to PsA. References: Tillett, W., C. de-Vries, and N.J. McHugh, Work disability in psoriatic arthritis: a systematic review. Rheumatology, 2012. 51(2): p. 275–283. Wallenius, M., et al., Work disability and health-related quality of life in males and females with psoriatic arthritis. Ann Rheum Dis, 2009. 68(5): p. 685–9. Disclosure of Interest: None declared